Natural occurrences and characterization of Elizabethkingia miricola infection in cultured bullfrogs (Rana catesbeiana) - Wei, Dongdong; Cheng, Yuan; Xiao, Shuangyan; Liao, Wenyu; Yu, Qing; Han, Shuyu; Huang, Shuaishuai; Shi, Jingu; Xie, Zongsheng; Li, Pengfei (Frontiers in Cellular and Infection Microbiology, 2023)
The bacterium, Elizabethkingia miricola, is known as one of the major pathogens associated with meningitis-like disease, but there are no reports of this bullfrog bacterium in Guangxi province. In the present study, the dominant bacteria was isolated from the brain of five bullfrogs having meningitis-like disease on one South China farm of Guangxi. The NFEM01 isolate was identified by Gram staining, morphological observations, 16S rRNA, rpoB and mutT based phylogenetic tree analysis, physiochemical characterization and subjected to drug sensitivity and artificial infection testing. As a result of identification, the NFEM01 was found to be E. miricola. An artificial infection experiment revealed that NFEM01 infected bullfrogs and could cause symptoms of typical meningitis-like disease. As a result of the bacterial drug sensitivity test, NFEM01 is highly sensitive to mequindox, rifampicin, enrofloxacin, nitrofural, oxytetracycline and there was strong resistance to gentamicin, florfenicol, neomycin, penicillin, amoxicillin, doxycycline and sulfamonomethoxine. This study provides a reference to further study the pathogenesis mechanism of E. miricola induced bullfrog meningitis-like disease and its prevention and treatment.